The SEC, the Audit Committee Rules, and the Marketplaces: Corporate Governance and the Future - Helen S. Scott (Washington University Law Quarterly, 2001)
The “Audit Committee Rules” (the Audit Rules) comprise an integrated set of regulations issued by the Securities Exchange Commission (the SEC), the marketplaces, and the accounting profession. The genesis of the Audit Rules was a determination by the SEC that the quality of the financial data reported by companies with publicly traded securities was susceptible to distortion (intentional or otherwise) in response to the pressures of the new, increasingly volatile and demanding marketplace. The SEC further determined that altering the information flow and relationships within a company and between the company and its outside auditors could minimize this potential for distortion. This change focused on the Audit Committee of the Board of Directors. Several different pieces of the overall puzzle, however, had to be changed to do this: the structure and function of the Audit Committee of the Board of Directors, the applicable independence standards or the company’s outside financial auditors, the relationship between the Audit Committee and the auditors, and the public disclosure of this information flow and review of the company’s financial statements.
Keywords: Audit committees; United States. Securities & amp; Exchange Commission; New York Stock Exchange Inc.; Accounting; Corporate governance; Securities